Perilaku Keuangan Memediasi Hubungan Hedonisme, Perencanaan Keuangan dan Stres Keuangan Terhadap Pengelolaan Keuangan Pribadi - Rezky Rahmawati; Sumastuti, Efriyani; Indriasari, Ika (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2026)
Personal financial problems are not only experienced by low-income individuals but also by salaried employees. This phenomenon also occurs among employees of PT Eclat Textile International, where some still struggle to manage their finances effectively. This study aims to analyze the influence of hedonism, financial planning, and financial stress on personal financial management, with financial behavior as a mediating variable. The research approach used quantitative methods through a survey of non-labor employees. Data were collected using a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results show that financial planning has a positive effect on financial behavior and personal financial management, while hedonism and financial stress tend to have a negative impact. Financial behavior has been shown to play a significant role as a mediator, strengthening the positive influence of financial planning and minimizing the negative impacts of hedonism and financial stress on personal financial management. These findings emphasize the importance of developing healthy financial behavior through education and habituation, so that employees can achieve long-term financial stability.